Electroclinical features of idiopathic generalised epilepsy with persisting absences in adult life. Issue 5 (November 1996) - Michelucci, R; Rubboli, G; Passarelli, D; Riguzzi, P; Volpi, L; Parmeggiani, L; Rizzi, R; Gardella, E; Tassinari, C A
Abstract : OBJECTIVES: To describe the electroclinical features of typical absences persisting in adult life. METHODS: Twelve adult patients (aged 21 to 56 years) with idiopathic generalised epilepsy featuring typical absences as the prominent clinical feature were studied. All patients underwent a full clinical and neurophysiological investigation including ictal documentation of seizures. RESULTS: Neurological examination and neuroradiological investigations were normal in all cases. Clinical findings included a median age at onset of absences of 14 (range 4-32) years, almost constant tonic-clonic seizures (in 83% of patients), frequent episodes of absence status (in 33% of patients), and associated cognitive or psychiatric disturbances. Interictal EEG findings showed normal background activity, generalised paroxysms of spike waves or polyspike waves, and inconstant focal spikes (in five patients); runs of polyspikes were seen during non-REM sleep. Ictal EEG findings showed generalised spike waves at 3 Hz, sometimes preceded by multiple spikes, or more complex EEG patterns with sequences of polyspikes intermingled with spike waves or polyspike waves, showing discharge fragmentation or variation of intradischarge frequency. CONCLUSION: The results of the present study show that absences persisting in adult life may show particular clinical and EEG patterns, distinct from those in childhood or adolescence.